Purification and Properties of a Neutral Protease from Soil Bacterium WM 122 - Papaioannou, S. E; Marsheck, W. J (Thrombosis and Haemostasis, 1977)
An extracellular protease SN 687, secreted by the soil bacterium isolate WM 122, has been purified by means of gel filtration, ammonium sulfate precipitation, DEAE-Sephadex and hydroxylapatite chromatography. Apparent homogeneity was ascertained by Polyacrylamide gel electrophoresis. The protease was inactivated by ethylenediamine tetracetic acid (EDTA) but not by diisopropylfluorophosphate (DFP), and it was partially inhibited by serum inhibitors. SN 687 was shown to be of high specific activity against casein and fibrin, but it did not hydrolyze L- lysine -methyl ester dihydrochloride (LME), p-tosyl-L-arginine-methyl ester hydrochloride (TAME) and N-benzoyl-L-tyrosine-ethyl ester hydrochloride (BTEE) synthetic substrates. The optimum pH for hydrolysis of casein was 7.5 and the molecular weight, as determined by gel filtration, was 31,000.